Monetary Policy Committees: Individual and Collective Reputations - Anne Sibert (Center for Economic Studies and ifo Institute (CESifo), 1999)
This paper looks at how the reputation of a monetary policy making committee is jointly determined with the reputations of its individual members. I ask whether individuals ha ve more or less incentive to gain a reputation for being tough on inflation when they are part of a group. I examine the effect of increased transparency - in the form of publishing the votes of individual members - on individuals' incentives to appear hard nosed. I look at how other institutional features of central banks affect the policy making body's incentive to refrain from inflation.
Keywords: 330; Reputation; collective decision making; central banks